Current issue in the Technical Vocational Education and Training (TVET) instructor - Asnul Dahar Minghat; Siti Salina binti Mustakim; Nuraini Shahroni (ASEAN Journal of Science and Engineering Education, 2023)
This paper explains current issues in the technical vocational education and training (TVET) instructor. This paper provides an overview of the TVET system, three elements of competency which are knowledge, skills, and attitudes, and the challenge of IR4.0. along with the research background, problem statement, and research question. The research objectives as derived from the problem background and problem statement are presented. The scope, significance, and conceptual framework of the research are also presented.